Development of Real-Time Fuzzy Synchronization of Chaos Based System for Image Encryption - Guler, Hasan (Int Information & Engineering Technology Assoc, 2021)
The concept of chaos, which has entered the literature since the 19th century, has been used for the protection of information with the development of information technologies in recent years. Chaos circuits are frequently used in secure communication systems because of its unpredictability and ease of modeling. In this paper, real-time fuzzy control method was used for master-slave synchronization of Rucklidge chaotic circuit. Also, sinusoidal signal and image encryption were used for application of secure communication process in LabVIEW platform. Data acquisition system was used to implement real time application. Fuzzy control performed synchronization at the end of the specified period and image encryption and decryption were successfully obtained in the developed system.
Keywords: chaotic circuit; synchronization; fuzzy; image encryption